2011
DOI: 10.1016/j.jfs.2009.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Regulations, competition and bank risk-taking in transition countries

Abstract: This study investigates whether regulations have an independent effect on bank risk-taking or whether their effect is channeled through the market power possessed by banks. Given a well-established set of theoretical priors, the regulations considered are capital requirements, restrictions on bank activities and official supervisory power. We use data from the Central and Eastern European banking sectors over the period 1998-2005. The empirical results suggest that banks with market power tend to take on lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
421
2
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 540 publications
(473 citation statements)
references
References 47 publications
44
421
2
6
Order By: Relevance
“…One study that supports this theory is the research conducted by Yeyati and Micco (2007), who state that in the banking sector of 8 Latin countries there was evidence of a positive relationship between competition and financial stability. In addition, the study by Arogaki et al (2011) also found evidence in the countries of Central and Eastern Europe that supports the idea that competition in the banking industry can improve stability. The research conducted by Boyd et al (2006) also came to the same conclusion, using samples from the United States and 134 other countries.…”
Section: Literature Reviewmentioning
confidence: 52%
“…One study that supports this theory is the research conducted by Yeyati and Micco (2007), who state that in the banking sector of 8 Latin countries there was evidence of a positive relationship between competition and financial stability. In addition, the study by Arogaki et al (2011) also found evidence in the countries of Central and Eastern Europe that supports the idea that competition in the banking industry can improve stability. The research conducted by Boyd et al (2006) also came to the same conclusion, using samples from the United States and 134 other countries.…”
Section: Literature Reviewmentioning
confidence: 52%
“…Several authors (Rime, 2001;Lin et al, 2005;Altunbas et al, 2007;Leaven and Levine, 2009) revealed that regulatory capital (CAR) is positively associated with bank risk. In contrast, others found an inverse relationship between regulatory capital and bank risk (Ho and Hsu, 2010;Agoraki et al, 2011;Lee and Chih, 2013). These studies support the -Moral hazard hypothesis (MHH),‖ which holds that banks with strong regulatory capital can absorb higher risk.…”
Section: Capital Adequacy Ratiomentioning
confidence: 61%
“…The Capital Adequacy Ratio (CAR) in Models I and II are negatively associated with bank default risk (NPLR) and are statistically significant (p<.01), similar to Ho and Hsu (2010); Agoraki et al (2011); Lee and Hsieh (2013);…”
Section: Baseline Modelsmentioning
confidence: 92%
“…Indeed, these authors showed that most regulators encourage banks to increase their capital compared to the risk level. However, the relationship between equity to total assets ratio and bank risk was found to be negative (Jahankhani and Lynge, 1980;Brewer and Lee, 1986;Karels et al, 1989;Jacques and Nigro, 1997;Bolt and Tieman, 2004;Agusman et al, 2008;Agoraki et al, 2011;Lee and Hsieh, 2013). Bolt and Tieman (2004) argued that capital requirement is a strict criterion for supplying loans.…”
Section: Bank Capital and Riskmentioning
confidence: 99%
“…Therefore, an institution with high level of capital find in its interest to take less risk. According to Agoraki et al (2011), banks holding more capital are less exposed to risk, but high market power may increase bank risk. Demirgüç-Kunt and Kane (2002) showed that a negative relationship between capital and risk is referred to the moral hazard hypothesis, which stipulates that undercapitalised banks take on excessive risk to exploit existing flat deposit insurance schemes.…”
Section: Bank Capital and Riskmentioning
confidence: 99%